Investigating animal activity patterns and temporal niche partitioning using camera‐trap data: challenges and opportunities. Issue 3 (18th August 2017) - Frey, Sandra; Fisher, Jason T.; Burton, A. Cole; Volpe, John P.
Abstract: Time‐stamped camera data are increasingly used to study temporal patterns in species and community ecology, including species' activity patterns and niche partitioning. Given the importance of niche partitioning for facilitating coexistence between sympatric species, understanding how emerging environmental stressors – climate and landscape change, biodiversity loss and concomitant changes to community composition – affect temporal niche partitioning is of immediate importance for advancing ecological theory and informing management decisions. A large variety of analytical approaches have been applied to camera‐trap data to ask key questions about species activity patterns and temporal overlap among heterospecifics. Despite the many advances for describing and quantifying these temporal patterns, few studies have explicitly tested how interacting biotic and abiotic variables influence species' activity and capacity to segregate along the temporal niche axis. To address this gap, we suggest coordinated distributed experiments to capture sufficient camera‐trap data across a range of anthropogenic stressors and community compositions. This will facilitate a standardized approach to assessing the impacts of multiple variables on species' behaviours and interactions. Ultimately, further integration of spatial and temporal analyses of camera‐trap data is critical for improving our understanding of how anthropogenic activities and landscape changes are altering competitive interactions and the dynamics of animal communities. Abstract : Within the last decade, camera‐trap data have been increasingly used to study species activity patterns and niche partitioning, as well as a large variety of methods to analyse the data. This review outlines the questions that may be asked from camera‐trap data regarding species activities, temporal niche partitioning and the abiotic and biotic variables which may influence species behaviours and interactions, and highlights those approaches where gains have been best made in improving our understanding of such processes. We also explore the future directions where our understanding of the combined spatiotemporal aspects of species niche partitioning and responses to emerging environmental stressors (e.g. climate and landscape changes, biodiversity loss, changes to community composition) can best be advanced.